Designing Teaching Materials - Yayra Abduraimova (International Journal on Integrated Education, 2022)
The article deals with the issues based on the process and requirements of designing appropriate teaching materials. Teaching materials - their format, accessibility, modernity - are an important and main component of the organization of the educational process. The emergence and successful development of an alternative model for the training of future foreign language teachers requires innovative activities in the development of teaching materials. Such materials should be characterized by “mobility”, which provides the student with the opportunity to use them outside the walls of the university and at a time convenient for the working person, and for creating conditions for the individualization of the educational process.